A Single 60 mg Dose of Denosumab Might Improve Hepatic Insulin Sensitivity in Postmenopausal Nondiabetic Severe Osteoporotic Women. (19th March 2015) - Passeri, Elena; Benedini, Stefano; Costa, Elena; Corbetta, Sabrina
Abstract : Background . The RANKL/RANK/OPG signaling pathway is crucial for the regulation of osteoclast activity and bone resorption being activated in osteoporosis. The pathway has been also suggested to influence glucose metabolism as observed in chronic low inflammation. Aim . To test whether systemic blockage of RANKL by the monoclonal antibody denosumab influences glucose metabolism in osteoporotic women. Study Design . This is a prospective study on the effect of a subcutaneously injected single 60 mg dose of denosumab in 14 postmenopausal severe osteoporotic nondiabetic women evaluated at baseline and 4 and 12 weeks after their first injection by an oral glucose tolerance test. Results . A single 60 mg dose of denosumab efficiently inhibited serum alkaline phosphatase while it did not exert any significant variation in fasting glucose, insulin, or HOMA-IR at both 4 and 12 weeks. No changes could be detected in glucose response to the glucose load, Matsuda Index, or insulinogenic index. Nonetheless, 60 mg denosumab induced a significant reduction in the hepatic insulin resistance index at 4 weeks and in HbA1c levels at 12 weeks. Conclusions . A single 60 mg dose of denosumab might positively affect hepatic insulin sensitivity though it does not induce clinical evident glucose metabolic disruption in nondiabetic patients.